A Variant of Leptin Gene Decreases the Risk of Gastric Cancer in Chinese Individuals: Evidence from a Case–Control Study - Ma R; He Q (Dove Medical Press, 2020)
Renjie Ma, Qi He Department of Infectious Disease, The People’s Hospital of Danyang, Affiliated Danyang Hospital of Nantong University, Danyang, Jiangsu Province, 212300, People’s Republic of ChinaCorrespondence: Qi He Tel/fax +86-511-86553015Email heqi3214@163.comBackground: A host of studies have explored the potential connection between leptin (LEP) G19A polymorphism and the risk of cancers, but the relationship between gastric cancer (GC) susceptibility and LEP G19A polymorphism was not revealed before. The aim of this study was to investigate this relationship in Chinese Han population.Methods: Thus, this case–control study with 380 GC cases and 465 controls was designed to unearth the link between LEP G19A polymorphism and GC susceptibility. Genotyping was accomplished by a custom-made 48-Plex SNP scanTM kit. Relative LEP gene expression was detected by real-time reverse transcription-polymerase chain reaction.Results: LEP G19A polymorphism was shown to relate with a decreased risk of GC. Subgroup analyses uncovered significant connections in the males, nondrinkers, and those at age < 60 years. G19A polymorphism was also linked with tumor size and location and pathological type of GC. Last, LEP gene expression in gastric tissues was considerably less than in control tissues.Conclusion: This study shows that G19A polymorphism of LEP gene is linked with a lower risk of GC in the tested Chinese Han individuals.Keywords: LEP, gastric cancer, G19A polymorphism, case-control study